Researching International Pedagogies
VI, 316 p.
Keywords: In our rapidly globalizing world students are able to access learning through mobility, through computer mediated experiences, and through the diverse perspectives of their peers and teachers. All of these components impact on the ways in which universities and their staff prepare and present courses for their students. This book presents an edited selection of chapters compiled under the theme of ‘new international pedagogies’. The objective is to document current pedagogical frameworks and practices in the teaching and learning context of international education. It showcases innovative teaching and learning methods, methodological frameworks and novel pedagogies that contribute to improving the effectiveness of teaching and learning in international settings and diverse student groups. The collection of seventeen chapters offers new debate on applied critical educational thought, innovation in teaching and learning, and culturally sensitive and inclusive curriculum practices across a broad disciplinary spectrum. Of central interest is the production of teaching and learning examples that provide evidence for implementing progress and advancement in the field. The book aims to stimulate further debate, research and application in the field of international pedagogies.